Study on the evolution of fruit prices at national level in the period 2015-2019 - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The scientific paper presents the evolution of national fruit prices in the period 2015-2019. Over time, fruit and vegetable prices have an increasing trend, and in this study I aimed to identify the factors that lead to this increase prices from one year to another. Regular consumption of fruits and vegetables has an important role in maintaining long-term health. Romanian fruits and vegetables even if they do not have a commercial appearance that meets consumer requirements have special nutritional qualities even if the price is higher than that of fruits imported from Greece, Italy, etc. The research method used in the study is statistical processing and economic analysis of existing data for the period 2015-2019 on specialized sites such as the National Institute of Statistics (INS), Eurostat , FAO, Ministry of Agriculture and Rural Development (MADR) but also other specialized materials.
Keywords: Q11; Q13; L11; 330; evolution; prices; grapes; plums; cherries